Costs and outcomes of Lynch syndrome screening in the Australian colorectal cancer population - Cenin, Dayna; Naber, S.; Lansdorp-Vogelaar, Iris; Jenkins, M.; Buchanan, D.; Preen, D.; Ee, H.; O'Leary, Peter (Wiley-Blackwell Publishing Asia, 2018)
© 2018 The Authors Journal of Gastroenterology and Hepatology published by Journal of Gastroenterology and Hepatology Foundation and John Wiley & Sons Australia, Ltd Background and Aim: Individuals with Lynch syndrome (LS) are at increased risk of LS-related cancers including colorectal cancer (CRC). CRC tumor screening for mismatch repair (MMR) deficiency is recommended in Australia to identify LS, although its cost-effectiveness has not been assessed. We aim to determine the cost-effectiveness of screening individuals with CRC for LS at different age-at-diagnosis thresholds. Methods: We developed a decision analysis model to estimate yield and costs of LS screening. Age-specific probabilities of LS diagnosis were based on Australian data. Two CRC tumor screening pathways were assessed (MMR immunohistochemistry followed by MLH1 methylation (MLH1-Pathway) or BRAF V600E testing (BRAF-Pathway) if MLH1 expression was lost) for four age-at-diagnosis thresholds—screening < 50, screening < 60, screening < 70, and universal screening. Results: Per 1000 CRC cases, screening < 50 identified 5.2 LS cases and cost $A7041 per case detected in the MLH1-Pathway. Screening < 60 increased detection by 1.5 cases for an incremental cost of $A25 177 per additional case detected. Screening < 70 detected 1.6 additional cases at an incremental cost of $A40 278 per additional case detected. Compared with screening < 70, universal screening detected no additional LS cases but cost $A158 724 extra. The BRAF-Pathway identified the same number of LS cases for higher costs. Conclusions: The MLH1-Pathway is more cost-effective than BRAF-Pathway for all age-at-diagnosis thresholds. MMR immunohistochemistry tumor screening in individuals diagnosed with CRC aged < 70 years resulted in higher LS case detection at a reasonable cost. Further research into the yield of LS screening in CRC patients = 70 years is needed to determine if universal screening is justified.